Right Vertebral Artery Transection With a Vertical Distraction of C5-6: Case Report of a Patient Survival. Issue 5 (May 2020) - Griffard, Jared; Bollig, Reagan
Spinal column injuries are very commonly diagnosed in the multitrauma population, and extensive distraction injuries are often fatal due to cerebrovascular injuries or spinal cord injuries. We present a 62-year-old female who presented after an MVC with a 2-cm vertical distraction injury of C5-6 with a right vertebral artery transection and left vertebral artery dissection. She received multidisciplinary treatment which resulted in her survival, albeit with severe neurologic deficits. We challenge the current literature that suggests a blunt vertebral artery transection is 100% fatal.